Vulnerability as a perceptual category – Martha Nussbaum’s capabilities approach from the perspective of political aesthetics - Lisowska, Urszula (Hybris, 2015)
The aim of the paper is to draw politico-aesthetic consequences from Martha Nussbaum’s capabilities approach. It is argued that this can be achieved by focusing on the notion of vulnerability implied by the idea of capabilities. The recognition of the vulnerability of the human good inspires a new model of practical rationality based on perception. This idea, in turn, explores the aesthetic connotations of perception implied by its etymology (the ancient Greek for perception being aesthesis). Thus, political aesthetics is understood as the inquiry into the political consequences of the affinity between ethics and aesthetics, as well as the political relevance of the notion of beauty.